Роль гідротехнічних споруд у запобіганні розвитку схилових ерозійно-гравітаційних процесів на урбанізованих територіях - Анацький, О.М. (Інститут геологічних наук НАН України, 2009)
Рассмотрены вопросы функционирования гидротехнических сооружений, предупреждения развития эрозионно-гравитационных процессов на склонах в г. Киев, их влияние на геологическую среду города. Склоны долин водотоков частично застроены, укреплены, а выходы подземных вод перехватываются дренажными системами. Особый акцент сделан на деятельности человека как главном факторе влияния на территорию его проживания. The question of functioning of hydraulic engineering constructions, preventions of development of erosive and gravitational processes on slopes in Kiev, their influence on the geological environment of city is considered. Some parts of the slopes of watercourses valleys have been built-up, consolidated and the outlets of the underground waters have been intercepted by the drainage systems. Special emphasis is made on human activity as the main factor which affects the area of human habitation.